Measurement of ionization, charge exchange and ion confinement times in charge breeder ECR ion sources with short pulse 1+ injection of metal ions. Issue 1 (1st April 2022) - Luntinen, M; Angot, J; Tarvainen, O; Toivanen, V; Thuillier, T; Koivisto, H
Abstract: The Consecutive Transients (CT) method is used for estimating the characteristic times of ionization, charge exchange and confinement within the plasma of a Charge Breeder Electron Cyclotron Resonance Ion Source (CB-ECRIS). The method reveals differences in the characteristic times between different source configurations, with K 9+ charge breeding efficiencies of 8.9 % and 20.4 %, and allows qualitative explanation of the improved breeding efficiency. The increase in K 9+ efficiency is accompanied by a decrease in ionization time for low charge states, a decrease of charge exchange time for high charge states, and an overall decrease of the ion confinement time, which increases non-linearly with the charge state. The charge exchange time exhibits a minimum near charge state K 8+, indicating low neutral density near the plasma core. The CT-method yields a distribution of possible ne and (Ee ) corresponding to the spatial distribution of different charge state ions. The results hint at a non-uniform plasma electron density and energy distribution as well as a nested-layer distribution for the ion populations — hot and dense plasma with high charge state ions near the plasma core.